MEDIA BREAK AND PUT UNTUK MENINGKATKAN HASIL BELAJAR MATERI REPORT TEXT - Imzinaryani Imzinaryani (Jurnal Didaktika Pendidikan Dasar, 2019)
This classroom action research is based on the low English score, especially on the writing skill aspect in Report Text material. The learners are lack confidence, feel saturated, and less interested to write in English. The research aims to increase the result of studying in writing the simple paragraph of Report Text in the first cycle and second cycle by using Break and Put Media. The research is carried out from January to April 2017 in Class IX of SMP Unggul Pidie Jaya. The study consists of two cycles, each cycle consists of two meetings. Each cycle consists of planning, implementation, observation, and reflection. Data collection techniques and tools used in this research are descriptive analysis techniques, in the form of documents of the learners’ paperwork, score list, and observation sheets. The results of the research indicate that Break and Put Media causes a fun learning situation so that there is an increase in student learning outcomes. The increase occurred from cycle I to cycle II. In the first cycle, the number of learners who received a complete score is 10 people or 47.21%  and the incomplete score is 11 learners or 52.38%. Meanwhile, in the second cycle, there is an increase of the complete score to 20 learners or 87% and an incomplete score to 3 learners or 13%. So, there is an increase of about 39.79% from cycle I to cycle II. The conclusion is the use of Break and Put Media can increase the learning outcomes of the learners in Class IX of SMP Unggul Pidie Jaya on Report Text material.